Persepsi Masyarakat Tentang Program Nasional Pemberdayaan Masyarakat Mandiri Perkotaan di Kecamatan Singkil Kota Manado - Kodoati, Raymond (JURNAL ILMIAH SOCIETY, 2015)
In the city of Manado in urban poverty reduction programs have been implemented since 2004, including in the district of Singkil. Of the various program implementation still poses various problems both of implementing itself or of public perception. This study was conducted to analyze public perception Singkil District of the city of Manado on the National Program for Community Empowerment Urban. The research method used in this study is qualitative.The results showed that the public perception Singkil District of Manado on the National Program for Community Empowerment Urban has undergone a change from project orientation to orientation goals. However, changes in the public's perception is not followed by the role of the Institute for Community Self-reliance in carrying out the task of mentoring. Advised him to undertake capacity building and functioning of the Institute for Community Self-Reliance in order to carry out the task of mentoring